Osteoid osteoma of the proximal phalanx of the hallux: a case report of a challenging diagnosis - Basile, Attilio; Liuni, Federico Maria; Fontanarosa, Alberto; Zoccali, Carmine; Baldi, Jacopo; Lanzetti, Riccardo Maria (Acta Biomedica Atenei Parmensis, 2020)
Osteoid osteoma is a benign bone lesion that accounts for approximately 10% to 12% of all benign bone tumors. More than 80% of lesions occur in patients between 5 to 25 years old; males are more commonly affected with a ratio of 3:1. The foot is rarely involved: its involvement is less than 4% in the foot and of 1.7% in the metatarsals. In this paper we discuss the case of a 27-years-old woman with a 12 months follow-up, presented with an osteoid osteoma of the proximal phalanx of the great toe that underwent an en-bloc excision of the lesion and subsequent filling with cancellous autograft from the ipsilateral calcaneus.